Pengaruh Leader-Member Exchange dan Motivasi pada Organizational Citizenship Behavior dengan Kepuasan Kerja sebagai Pemediasi - Nur Tifa Rachmawati; Ignatius Soni Kurniawan; Nala Tri Kusuma (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The study aims to determine the effect of leader-member exchange (LMX) and work motivation on organizational citizenship behavior (OCB) with mediation of job satisfaction at PT Adi Satria Abadi Yogyakarta. By using a population of PT Adi Satria Abadi employees with a sample size of 80 respondents. The sampling technique used accidental sampling. Data obtained through questionnaires and processed by classical assumption tests and multiple linear regression analysis, as well as the sobel test. So the conclusion is that LMX and work motivation have a significant positive effect on job satisfaction. LMX variables and job satisfaction are not significant on OCB. Work motivation variables have a significant positive effect on OCB. Job satisfaction does not mediate the LMX and work motivation on OCB. The object in this study only covers one branch of PT Adi Satria Abadi Yogyakarta.